2015
DOI: 10.3389/fmicb.2015.00002
|View full text |Cite
|
Sign up to set email alerts
|

Use of lanthanides to alleviate the effects of metal ion-deficiency in Desmodesmus quadricauda (Sphaeropleales, Chlorophyta)

Abstract: Lanthanides are biologically non-essential elements with wide applications in technology and industry. Their concentration as environmental contaminants is, therefore, increasing. Although non-essential, lanthanides have been proposed (and even used) to produce beneficial effects in plants, even though their mechanisms of action are unclear. Recently, it was suggested that they may replace essential elements. We tested the effect of low concentrations of lanthanides on the common freshwater microalga Desmodesm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
37
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(43 citation statements)
references
References 64 publications
4
37
0
2
Order By: Relevance
“…Very recently, a vacuole‐like compartment was identified in E. huxleyi , where Ca 2+ and Sr 2+ are stored before being dispatched to build the coccoliths in the coccolith vesicle 14,42. If the terbium ions used in our study also take this pathway into the coccolith is speculative, but seems likely since the Tb 3+ are regarded as substitutes for Ca 2+ in the metabolism of microalgae as previously reported 16,30. Further investigations on the underlying biomineralization process in E. huxleyi for generating calcite coccoliths with incorporated Tb 3+ are needed.…”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…Very recently, a vacuole‐like compartment was identified in E. huxleyi , where Ca 2+ and Sr 2+ are stored before being dispatched to build the coccoliths in the coccolith vesicle 14,42. If the terbium ions used in our study also take this pathway into the coccolith is speculative, but seems likely since the Tb 3+ are regarded as substitutes for Ca 2+ in the metabolism of microalgae as previously reported 16,30. Further investigations on the underlying biomineralization process in E. huxleyi for generating calcite coccoliths with incorporated Tb 3+ are needed.…”
Section: Resultssupporting
confidence: 61%
“…Even though lanthanides are nonessential elements, they are taken up by microalgae and can have stimulatory effects 30. They can replace Ca 2+ in the cells and it was suggested that Ca 2+ transporters play a role in the internalization of these elements into microalgae 30,31. Different lanthanides accumulate in different parts of the cells 32.…”
Section: Introductionmentioning
confidence: 99%
“…According to Chaturvedi et al (2014), the application of 5–50 μM La in Vigna radiata, V. mungo , and maize increased the concentrations of chlorophylls a, b and total. This response is explained by the fact that La may substitute Mg 2+ during the formation of chlorophyll molecules (Hong et al, 2002; Goecke et al, 2015) and therefore more atoms for the formation of the chlorophyll molecule could be available in the growth medium. Furthermore, La may change the morphology of the external membrane of the chloroplast, which improves the structure of the organelle and leads to a higher concentration of functional nutrients such as N in the chloroplast (Hu et al, 2016b).…”
Section: Discussionmentioning
confidence: 99%
“…랫드에 34 mg/kg으로 기관내 투여한 결과에서는 산화란탄 > 산화네오디뮴 > 산화 세륨의 순으로 독성이 높게 나타났고 (Takaya et al, 2005), 마우스에 희토류를 30일간 반복 경구 투여하였 을 때에는 염화세륨 > 염화네오디뮴 > 염화란탄의 순 으로 독성이 높게 나타났다 (Cheng et al, 2014). 해조류 및 식물성장에 있어 희토류의 생체축적 및 부작용이 보고된 반면 (Carpenter et al, 2015), 몇몇 연구에서는 포유동물세포, 해조류 및 미세소기관에 서 희토류와 관련한 촉진 효과가 보고되고 있다 (Jenkins et al, 2011;Liu et al, 2012;Pol et al, 2014;Goecke et al, 2015). …”
Section: 에 따르면 희토류 시장규모는 1964년부터 1997년까unclassified